Internet-based self-administered intervention to reduce anxiety and depression symptomatology and improve well-being in 7 countries: protocol of a randomized control trial - Dominguez-Rodriguez, Alejandro; Herdoiza-Arroyo, Paulina Erika; González-Ramírez, Leivy Patricia; Martínez-Arriaga, Reyna Jazmín; Villarreal-Zegarra, David; Santos da Silva, Antonio Carlos; González-Cantero, Joel Omar; Vargas Salinas, Viviana Sylvia; S. Mensorio, Marinna; Cisneros Hernández, Adrián Antonio; Lourenço dos Santos, Rogéria; Nieto Ramos, Emilia Gabriela; et al. (Frontiers in Psychology, 2024)
Background: Online psychological interventions have emerged as a treatment alternative because they are accessible, flexible, personalized, and available to large populations. The number of Internet interventions in Latin America is limited, as are Randomized Controlled Trials (RCTs) of their effectiveness, and only some studies compare their effectiveness in multiple countries simultaneously. We have developed an online intervention, Well-being Online, which will be available to the public free of charge in 7 countries: Mexico, Ecuador, Peru, Chile, Brazil, Spain, and the Netherlands. We expect a reduction in depression and anxiety symptoms and an increase in the well-being of the participants. Methods: A multi-country randomized controlled trial will be conducted. The intervention is multicomponent based on Cognitive Behavioral Therapy, Behavioral Activation Therapy, Mindfulness, Acceptance and Commitment Therapy, and Positive Psychology, and has ten sessions. In each country, eligible participants will be randomized to one of three groups: Enriched Intervention (interactive web design with videos, infographics, text, audio, and forum), Text Intervention (text on the website), and Wait List (control group). Repeated measures will be obtained at 5-time points. Our primary outcomes will be anxiety and depressive symptomatology and mental well-being. MANOVA analysis will be used for our main analysis. Discussion: This protocol describes the design of a randomized trial to evaluate the efficacy of a web-based intervention to reduce anxiety and depression symptomatology and increase subjective well-being. The intervention will be available in four languages (Spanish, Portuguese, Dutch, and English). Its results will contribute to the evidence of effectiveness in terms of randomized trials and Internet interventions, mainly in Latin America and Europe. Ethics and Dissemination: The study counts currently with the approval of the ethics committee of the Universidad Autónoma de Ciudad Juárez, Mexico (CEI-2022-2-761), the ethics committee of the Universidad Europea de Valencia, Spain (CIPI/23.084), the ethics committee of Fundação de Ensino e Pesquisa em Ciências da Saúde, Brazil (CAAE: 65631922.3.0000.5553), and the Research Ethics Committee of the César Vallejo University